Rasm al-Qur'an dan Bentuk-Bentuk Penulisannya - Badrudin Badrudin (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2016)
Abstract